ダイ 29 ジ ナンキョク チイキ カンソク タイ キスイケン ブモン エットウ ホウコク 1988 - 和田, 誠; ワダ, マコト; 青木, 周司; アオキ, シュウジ; 青木, 輝夫; アオキ, テルオ; 瀬古, 勝基; セコ, カツモト; Wada, Makoto; Aoki, Shuhji; Aoki, Teruo; Seko, Katsumoto (1990)
P(論文) 南極域における気候変動に関する総合研究(Antarctic Climate Research : ACR)が1987年(第28次南極地域観測隊)より5ヵ年計画で開始された。第29次観測隊気水圏部門ではこの計画に沿って, 大気状態の年々変動, 特に1)雲と降水の変動の観測, 2)大気微量成分のモニタリング, を重点項目として観測を行った。また, あすか観測拠点では定常気象観測, 大気放射等の観測を行った。このほか, 無人気象観測点の新設, 海氷, 氷床上の観測を実施した。これらの観測の経過状況, 観測結果の概要について報告する。 A 5-year project of "Antarctic Climate Research (ACR)" has been started from the 28th Japanese Antarctic Research Expedition (JARE-28) in 1987. In 1988 (JARE-29), 2 major items of observation were carried out under the subject of interannual variation of Antarctic atmosphere. 1) Observations of cloud and precipitation using vertical pointing meteorological radar, dual-wave microwave radiometer and NOAA satellite data. 2) Monitoring of atmospheric minor constituents. At Asuka Station surface synoptic observations and radiation measurements were made. Moreover, 2-unmanned stations were newly built and some other observations on the sea-ice and ice-sheet were carried out. departmental bulletin paper